Clinical Pharmacokinetics and Drug‐Drug Interaction Potential for Coadministered SCY‐078, an Oral Fungicidal Glucan Synthase Inhibitor, and Tacrolimus - Wring, Stephen; Murphy, Gail; Atiee, George; Corr, Christy; Hyman, Michele; Willett, Michael; Angulo, David (Clinical pharmacology in drug development, 2019)
SCY‐078 is an orally bioavailable triterpenoid glucan synthase inhibitor in clinical development as an intravenous and oral treatment of fungal infections caused by Candida and Aspergillus species. This was a sequential, single‐center, open‐label phase 1 study to assess the drug‐drug interaction potential between SCY‐078 and tacrolimus during concomitant administration in healthy subjects. In cohort 1, period 1, subjects received a single oral dose of tacrolimus 2 mg in the fasted state. In period 2 after a ≥15 day washout, subjects received a single loading dose of SCY‐078 1250 mg on day 1 followed by maintenance doses of SCY‐780 750 mg on days 2 through 8. On day 3 of period 2, subjects also received a single dose of tacrolimus 2 mg concurrent with SCY‐078. In cohort 2, subjects received a loading dose of SCY‐078 1250 mg on day 1 followed by maintenance doses of SCY‐780 750 mg on days 2 and 3. Pharmacokinetic (PK) parameters were compared to assess both the impact of steady‐state SCY‐078 on tacrolimus and the impact of tacrolimus on the PK of steady‐state SCY‐078. The concurrent coadministration of tacrolimus and SCY‐078 had no effect on the maximum blood levels of tacrolimus, as evidenced by no change in maximum concentration of drug in blood plasma and a 1.4‐fold increase in total area under the plasma drug concentration–time curve. The concurrent coadministration of tacrolimus and SCY‐078 resulted in a weaker interaction than typically observed with the azole class of antifungals. The current data indicate that an initial dose adjustment for tacrolimus may not be warranted when combined with SCY‐078, as the modest increase in exposure is less than the therapeutic window, although tacrolimus monitoring, as with addition of any new medication, is recommended. These results support the coadministration of SCY‐078 and tacrolimus.